Powder [videorecording (DVD)] - Salva, Victor; Steenburgen, Mary; Flanery, Sean Patrick; Henriksen, Lance, 1940-; Goldsmith, Jerry (Hollywood Pictures Home Video : Distributed by Buena Vista Home Entertainment, 2003)
A teenager with strange electromagnetic powers rises above prejudice from those frightened by his unusual appearance & abilities, touching the lives of those around him.